Engineering Iron Oxide Nanoparticles for Biomedicine and Bioengineering Applications - Urquijo, Jeaneth Patricia (2014)
In the present study the one-step coprecipitation method is used to obtain magnetic nanoparticles at controlled pH of 10 and 12, and surfactant concentration of 1% and 3%(m/m). The surfactant is sodium polyacrylate(PS), biocompatible and biodegradable, necessary attributes for biological applications. The magnetic nanoparticles have a magnetite core, and a shell of maghemite surrounded by a shell of polymer. The maghemite layer is smaller for large surfactant concentration(3%) and pH 10. The TEM images confirm the particle size distribution in the average range of 5-10 nm. Mössbauer results at 80 K showed line shapes dominated by magnetic relaxation effects with sextets and combinations of sextets and doublets for pH 12. The doublet features dominated the samples obtained at pH 10. The interactions of the surfactant with the nanoparticle surface, mainly with the Fe3+, is strong showing at least two surfactant layers, one layer directly over the nanoparticle surface and another layer resting over the inner layer. FTIR confirmed the attachment of the surfactant to the magnetic nanoparticle surface. The nanoparticles showed superparamagnetic behavior at room temperature and ferromagnetic properties at 5 K. The saturation magnetization presented lower values than reported bulk systems due to the presence of a large layer of maghemite. The very close particle size for all samples gave indication that the particle growth was dominated by the surface properties of the nanoparticles and that the pH and surfactant concentration did not affect importantly the growth process.